Barriers to and facilitators of HIV serostatus disclosure to sexual partners among postpartum women living with HIV in South Africa - Adeniyi, Oladele Vincent (BMC Public Health, 2021)
BACKGROUND: Disclosure of HIV serostatus to a sexual partner can facilitate partner’s support and testing and better treatment outcomes. Studies examining changes in disclosure rates of serostatus from delivery and postpartum periods are scarce. Our study fills this gap by using a follow-up survey of postpartum women with HIV to examine if disclosure prevalence has improved compared to the proportion recorded at childbirth. We further assessed the reasons for non-disclosure and correlates of serostatus disclosure to sexual partners. METHODS: We conducted a cross-sectional analytical study (exit interview) with a final sample of 485 postpartum women with HIV drawn from the East London Prospective Cohort study database between January and May 2018. Disclosure of HIV status to partner was based on self-reporting. We fitted adjusted and unadjusted logistic regression models and also conducted descriptive statistical analyses. Sampling weights were used to correct for sampling errors. RESULTS: Overall, 81.8% of women in the study cohort had disclosed their status to their partners, representing a 7.4 percentage point increase since child delivery. After adjusting for important covariates, women were more likely to disclose their status if they were married [adjusted odds ratio (AOR): 3.10; 95% confidence interval (CI):1.39–6.91] but were less likely to disclose if they used alcohol [AOR: 0.61; 95% CI:0.37–0.99] or had reported adherence to ART [AOR: 0.59; 95% CI:0.36–0.96]. Fear of rejection, stigma or being judged, new or casual relationships, and having a violent partner were the main reasons for not disclosing HIV status to sexual partners. CONCLUSION: We found a relatively higher rate of HIV status disclosure in the cohort compared to the rate recorded at childbirth, suggesting an improvement over time. Also, complicated relationship dynamics and fear of social exclusion still constitute barriers to HIV status disclosure to sexual partners despite patients’ counselling. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10955-x.